Application of Fuzzy Service Quality Method in Measuring Student Service Satisfaction Level - Ahmad Lubis Ghozali; Budi Warsito; Moh Ali Fikri (Jurnal Teknologi Pendidikan)
University services can be evaluated based on the quality of performance provided by faculty, administrative staff, and supporting institutional structures. Ensuring student satisfaction and minimizing complaints related to campus facilities are essential in enhancing the quality of higher education. This study aims to develop a method for measuring student satisfaction with campus services at Indramayu State Polytechnic using the fuzzy SERVQUAL technique. Data were collected through a questionnaire distributed to 100 students from three majors: Engineering, Informatics, and Nursing. The instrument used was both valid, with a 5% significance level, and reliable, as shown by a Cronbach's alpha score of 0.746. Data analysis involved comparing the gap between students’ perceptions and expectations across five service quality dimensions: tangibility, reliability, responsiveness, assurance, and empathy. The analysis revealed the largest gap in tangibility and the smallest in empathy. These findings indicate that while certain service aspects meet student expectations, others still require significant improvement. The results are expected to provide valuable input for the campus to enhance service quality and better align institutional performance with student needs. It is recommended that continuous evaluation and improvement efforts be implemented, particularly in the most critical service dimensions.